Municipal solid waste management policy of Parepare City - Lukman, Abam (FIA UB, 2017)
Municipal solid waste management policy still be a big problem in developing worlds. However, How to deliver and implement policy is still debatable. This study examines how the strategy of the municipal city in Managing Municipal Waste in Parepare City, South Sulawesi Province, Indonesia. This study laid the Edward III ‘ theory in adressing the implementation of policy base on 4 (four) major factors: communication, resources, disposition, and bureaucratic structure. This study examines the strategy of Parepare city government in combating muncipal waste under those 4 (four) aspect. Data come from the 5 key informants and other official municipal is statistics of Parepare city. Results of this study show that communication, resources, disposition, and bureaucratic structure significantly interrelate each other and support the strategic in implementing the policy in municipal waste management of Parepare City. The findings suggest that communication, fitting bureacratic structure, use of technology, and works in strategy through better collaboration among city agencies, and strengthening citizens’ awareness in winning and regaining beautiful city award, as like Adipura.